Clinical significance of HMGB1 changes and its role in targeted activation of TLR/NF-κB pathway in patients with lupus nephritis - PAN Hong-mei; ZHOU Guang-jun; MA Jin-rong; ZHANG Hong-ying; GUO Wei-yi (Linchuang shenzangbing zazhi)
Objective To study the clinical significance of high mobility group protein box 1(HMGB1) changes and its role in targeted activation of Toll-like receptor(TLR)/nuclear factor-κB(NF-κB) pathway in patients with lupus nephritis(LN).Methods LN patients admitted to our hospital from January 2015 to December 2018 were selected as LN group, and SLE patients without renal impairment visiting our hospital in the same period were selected as simple SLE group, healthy persons whose general information matched with the above patients during the same period were selected as control A group. Patients who received nephrectomy due to trauma and whose general information was comparable were selected as control B group. The levels of serum HMGB1 were detected by ELISA method, and the expressions of HMGB1, TLR2, TLR4 and NF-κB in kidneys were detected by immunohistochemistry. The targeted binding of HMGB1 to TLR2 and TLR4 in kidneys was verified by co-immunoprecipitation. Results The serum contents of HMGB1 in the LN group were significantly higher than those in the simple SLE group, control A group A and control B group(P<0.05). The average optical densities of HMGB1, TLR2, TLR4 and NF-κB in kidney in the LN group were significantly higher than those in the control B group(P<0.05). The eGFR level in LN patients with positive expression of HMGB1 was significantly lower than that in LN patients with negative expression of HMGB1(P<0.05), and the 24-hour urinary protein amount and SLEDAI score were significantly higher than those in LN patients with negative expression of HMGB1(P<0.05). According to co-immunoprecipitation, HMGB1 was targeted to bind to TLR2 and TLR4.Conclusions The high expression of HMGB1 may relate to the occurrence and progression of lupus nephritis, and targeted activation of the TLR/NF-κB pathway is a possible mechanism.